Mental Health Outcomes Among Healthcare Workers and the General Population During the COVID-19 in Italy - Rossi, Rodolfo; Socci, Valentina; Pacitti, Francesca; Mensi, Sonia; Di Marco, Antinisca; Siracusano, Alberto; Di Lorenzo, Giorgio (Frontiers in Psychology, 2020)
Background During the COVID-19 pandemic, healthcare workers in Italy have been exposed to an unprecedent pressure and traumatic events. However, no direct comparison with the general population is available so far. The aim of this study is to detail mental health outcomes in healthcare workers compared to general population. Methods 24050 respondents completed an on-line questionnaire during the contagion peak, 21342 general population, 1295 second-line healthcare workers and 1411 front-line healthcare workers. Depressive, anxious, post-traumatic symptoms and insomnia were assessed. Specific COVID-19 related potential risk factors were also considered in healthcare workers. Results Depressive symptoms were more frequent in the general population (28.12%) and front-line healthcare workers (28.35%) compared to the second-line healthcare workers (19.98%) groups. Anxiety symptoms showed a prevalence of 21.25% in the general population , 18.05% for second-line healthcare workers and 20.55% for front-line healthcare workers. Insomnia showed a prevalence of 7.82%, 6.58% and 9.92% for the general population , second-line healthcare workers and front-line healthcare workers, respectively. Compared to general population , front-line healthcare workers had higher odds of endorsing total trauma-related symptoms. Both second-line healthcare workers and front-line healthcare workers had higher odds of endorsing core post-traumatic symptoms compared to the general population , while second-line healthcare workers had lower odds of endorsing negative affect and dissociative symptoms. Higher total traumatic symptom score was associated with being a front-line healthcare workers, having a colleague infected, hospitalized or deceased, being a nurse, female gender and younger age. Conclusions This study suggests a significant psychological impact of the COVID-19 pandemic the Italian general population and healthcare workers. Front-line healthcare workers represent a specific at-risk population for post-traumatic symptoms. These findings underline the importance of monitoring and intervention strategies.